Experimental Study on the Effect of Supercritical CO2 on Mechanical Properties and Fracture Characteristics of Longmaxi Shale - Ran Zhang; Hao Yan; Lin Yang; Kun Liao; Lei Tao (Advances in Materials Science and Engineering)
Conventional hydraulic fracturing techniques typically consume large amounts of water when producing shale gas. Fracking fluids may cause environmental pollution. In contrast, supercritical carbon dioxide (scCO2) (above 31.8°C, 7.29 MPa) can displace CH4 in shale reservoirs. Achieve CO2 sequestration while increasing the shale gas production. We studied the mechanical properties and fracture characteristics of a shale under the action of scCO2, nitrogen, helium, and water by comparing the triaxial compression tests of shale samples with seven coring angles. The results show that: (1) scCO2 effectively reduced compressive strength of the shale and weakened the anisotropy of shale; (2) scCO2 caused the content of dolomite, calcite, and illite to decrease by 4.7%∼13.5%, respectively; (3) scCO2 produced micropores and microfractures 10 times larger than the original size in the microstructure. These microstructures can help improve the seepage and gathering of shale gas, leading to enhanced shale gas recovery and CO2 storage.